Knowledge, attitude and performance of dentists in Shiraz in relation to AIDS - Golsa Madadi; Anahita Safari; Reza Darafshi; Mitra Farzin; Mahroo Vojdani (Isfahan University of Medical Sciences, 2012)
Introduction: Health care workers and dental practitioners are always concerned about occupational transmission of human immunodeficiency virus (HIV). This study evaluated knowledge, attitudes and performance of dental practitioners in Shiraz, Iran in relation to AIDS. Materials and Methods: In this descriptive cross-sectional survey a 45-item questionnaire was distributed among 68 general and specialist dental practitioners in Shiraz. Data were analyzed by SPSS software using t-test, ANOVA and Pearson's correlation coefficient (α = 0.05). Results: The response rate was 88% (n = 60). The mean of dentists' knowledge was 8.9 ± 1.9 out of 13 and the mean of dentists' performance was 10.15 ± 3.2. The difference between males and females were not significant (p value = 0.51). Knowledge of dentists was significantly associated with age, i.e. there was a decrease in knowledge (p value = 0.03) and an improvement in performance (p value = 0.001) with an increase in age. A total of 93.3% of respondents felt an obligation to treat HIV-positive patients; 70% of dentists believed that the risk of HIV infection was high despite the necessary precautions. I relation to questions about attitude, no significant differences were observed between the respondents (p value = 0.29). Conclusion: Based on the results of the present study, the dental practitioners evaluated had a low level of knowledge and performance in relation to AIDS. It is necessary to improve knowledge, attitude and infection control behaviors of dental practitioners in relation to AIDS. It is suggested that more emphasis be placed on this subject in dental school curricula. Key words: AIDS, Attitude, Dentists, Knowledge, Performance.